Is Biomass a Reliable Estimate of Plant Fitness? - Younginger, Brett S; Sirová, Dagmara; Cruzan, Mitchell B; Ballhorn, Daniel J (Applications in plant sciences, 2017)
The measurement of fitness is critical to biological research. Although the determination of fitness for some organisms may be relatively straightforward under controlled conditions, it is often a difficult or nearly impossible task in nature. Plants are no exception. The potential for long-distance pollen dispersal, likelihood of multiple reproductive events per inflorescence, varying degrees of reproductive growth in perennials, and asexual reproduction all confound accurate fitness measurements. For these reasons, biomass is frequently used as a proxy for plant fitness. However, the suitability of indirect fitness measurements such as plant size is rarely evaluated. This review outlines the important associations between plant performance, fecundity, and fitness. We make a case for the reliability of biomass as an estimate of fitness when comparing conspecifics of the same age class. We reviewed 170 studies on plant fitness and discuss the metrics commonly employed for fitness estimations. We find that biomass or growth rate are frequently used and often positively associated with fecundity, which in turn suggests greater overall fitness. Our results support the utility of biomass as an appropriate surrogate for fitness under many circumstances, and suggest that additional fitness measures should be reported along with biomass or growth rate whenever possible.